Through the lens : barriers in research productivity - Rivera, Eloisa Alvaro (Saint Louis College, City of San Fernando, La Union : [s.n.], 2018)
The qualitative study using the case study design explored the barriers in research productivity among public elementary school teachers in the Division of La Union as basis in developing a validated research seminar for public elementary school teachers. The study identified the respondents' profile along highest educational attainment, number of years in teaching, number of years in teaching as Teacher III, number of seminars attended in research, and number of researches completed through documentary analysis. The study probed into the barriers encountered by the teachers in accomplishing research through face to face semi-structured interview. The salient findings were: most of the respondents have earned units in graduate studies; they also have been in the service from 5 to 25 years and have been serving as Teacher III for at most 5 years. Majority of the respondents have not attended any seminar in research. The research productivity of the public elementary schools in the Division of La Union was influenced by research-essential barriers along capability, support and intrapersonal aspects. The research seminar for Public Elementary School Teachers can address the identified barriers in undertaking scientific activities.
Bibliography: pages 123-128.
CHED-La Union
Keywords: Research ethics